What can agricultural biodiversity do in the fight against climate change? - Bioversity International (Bioversity International, 2015)
One of the main challenges that farmers have in the context of climate change is its unpredictability. Farmers can no longer rely on the timing of seasons and the availability of rainfall to see them through the year. Using agricultural biodiversity in the fight against climate change is about responding to variety with variety. Diversity can help farmers mitigate, adapt and ensure food (and nutrition) security, by providing them with more options to manage climatic risks, and strengthen the resilience of their farms and surrounding landscapes. These fact sheet contains some examples of how farming communities can use agricultural biodiversity to be climate-smart.